The Effect of Papain Enzyme Against Collagen Density in Keloid Tissue Culture - Herman Y. L. Wihastyoko (Journal of Global Pharma Technology, 2019)
Objective: Papain enzyme in Papaya sap has the ability to increase collagen degradation, thus, it can be used for the treatment of keloid. Therefore, the aim of this study was to determine the effect of this enzyme on keloid tissue. Methods: Randomized Controlled Trial Post-Test Only Design using ten human keloid tissues was applied in this research. Each of the tissue was divided into four treatment groups. The histological preparation was conducted by Masson’s trichrome staining. All of the samples were observed using a microscope. The collagen density was determined through the use of Olyvia software. The hydroxyproline level was measured by total collagen kit assay using a spectrophotometer. All the results were analyzed using a one-way ANOVA test. Result and Discussion: The mean value of collagen density in group K = 193,273+4,099; P1 = 188,765±3,598; P2 = 187,217±2,839; and P3 = 185.143±2.871. The results of statistical tests (p <0.05) on collagen density mean value showed that there is a significant difference between groups K, P1, P2, and P3. The mean value of hydroxyproline levels in group K = 268.5±69.43; P1 = 389,1±43,58; P2 = 454.8±85.81; and P3 = 559.8±167.57. The results of statistical tests (p<0.05) on hydroxyproline groups also showed a significantly difference in the groups. Conclusion: The papain enzyme can decrease the collagen density in keloid tissue culture.Keywords: Collagen density, hydroxyproline, keloid, papain enzyme